A199 BLACK ESOPHAGUS: AN UNDER-RECOGNIZED CAUSE OF UPPER GASTROINTESTINAL BLEEEDING. (26th February 2020) - Arora, A; Tsoi, K
Abstract: Background: "Black esophagus" is a term that refers to the endoscopic manifestation of acute esophageal necrosis (AEN), a rare but potentially under-recognized cause of upper gastrointestinal bleeding, characterized by the presence of strikingly black necrotic esophagus on upper endoscopy. The etiology is unclear although ischemic insults and caustic injury from gastric acid exposure are thought to play prominent roles. This condition is often seen in patients who are systemically unwell and have underlying comorbidities such as diabetes mellitus and vascular diseases. Aims: We present a case of an elderly woman with diabetes and poor glycemic control who developed coffee ground emesis with her upper endoscopy revealing evidence of acute esophageal necrosis. AEN is an important diagnosis to consider in diabetic patients, as it generally carries a poor prognosis with mortality rates as high as 32% reported in the literature. Methods: Case report and review of the literature Results: A 61-year-old woman with medical history significant for poorly controlled insulin dependent diabetes (hemoglobin A1c, 11%) developed coffee ground emesis (confirmed via insertion of nasogastric tube) three days after initial admission to hospital for left tibial plateau fracture. Her bloodwork did not reveal any underlying diabetic ketoacidosis or hyperosomlar hyperglycemic state. Her esophagogastroduodenoscopy (EGD) showed black, necrotic-appearing discoloration of the esophageal mucosa circumferentially within the mid to distal part of the esophagus with a sharp transition point towards normal appearing mucosa at the gastroesophageal junction. Biopsies were deferred due to high risk of bleeding and perforation, and the previously placed nasogastric tube was not removed. After endoscopy, conservative management was advised with restricted oral intake, intravenous proton pump inhibitor (PPI) inhibitor therapy for 72 hours and aggressive treatment of ongoing hyperglycemia. There were no signs or symptoms of esophageal rupture. The patient gradually recovered and in fact had her orthopedic surgery within a week of EGD. Furthermore, three days into the post operative period she developed venous thromboembolism and was placed on full dose oral anticoagulation and tolerated this without any further gastrointestinal bleeding. Conclusions: AEN is an important diagnostic consideration in elderly diabetic patients presenting with acute upper gastrointestinal bleeding, particularly as timely recognition and management can significantly lower the unfavorable mortality associated with this condition. Funding Agencies: None